Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Moderating Pada Dinas Perumahan Dan Kawasan Permukiman Kota Metro - Suwarto; Suryadi; Sari, Intan Novita (Jurnal Manajemen DIVERSIFIKASI, 2024)
Based on the previous observation which yielded the initial data regarding to the level of achievement on the employee performance, it turned out that it still did not fully show good achievement. An institution needs a leader who is able to provide direction to his subordinates where one of the goals is to direct all employees for obeying the rules have been made in order to make the employee performance increase. For this reason, it is necessary to have a quality leader so that later on he is able to lead his subordinates well so that, the organizational goals can be achieved effectively and efficiently. This study aimed at determining whether the leadership style of a leader influenced the employee performance, to determine whether work discipline effects employee performance, to determine whether the leadership style and work discipline affect the job satisfaction as a moderating variable and to determine whether work discipline influences job satisfaction as a moderating variable. The sample of this research was the employees of the Housing Department and Residential Areas of Metro City with totaling 59 employees. The collected data were carried out by distributing questionnaires. Furthermore, the collected data were analyzed by applying the Validity Test, Reliability Test, Data of Frequency Distribution, Normality Test, Linearity Test, Homogenia Test, Multiple Linear Regression Analysis, T Test, Coefficient of Determination Test, MRA Interaction Test and Statistical Hypothesis test using program (SPSS 25). The results of this study showed that there was a positive and significant influences between Leadership style on Employee Performance, there was a Positive and Significant influence between Work Discipline and Employee Performance, there was a positive and significant influence of Leadership Style between Employee Performance and Job Satisfaction as a Moderating Variable, there was a positive and significant influence Significance of Work Discipline and Employee Performance on Job Satisfaction as a Moderating Variable. Keywords: Leadership Style, Work Discipline, Employee Performance, Job Satisfaction.